2014
DOI: 10.1080/09540121.2014.963015
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing HIV-positive persons who use drugs and their families in Vietnam

Abstract: It is hypothesized that persons who use drugs (PWUD) in Vietnam who are also HIV-positive may face additional challenges in psychosocial outcomes, and these challenges may extend to their family members. In this study, we examined depressive symptoms, stigma, social support, and caregiver burden of HIV-positive PWUD and their family members, compared to the outcomes of HIV-negative PWUD and their family members. Baseline, 3-month, and 6-month assessment data were gathered from 83 PWUD and 83 family members rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…Although most participants in this study were heterosexual, which can be justified by the stimulus to early sexuality and the possibility of paid sex (26) , homosexuals are the ones who are strongly stigmatized and linked to large manifestations of exclusion and blamed for HIV infection (22,27) ; this is similar to what happens with drug users, being labelled and socially excluded (6,18,22,27) . We found that interruption of ART was not predominant in this study.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although most participants in this study were heterosexual, which can be justified by the stimulus to early sexuality and the possibility of paid sex (26) , homosexuals are the ones who are strongly stigmatized and linked to large manifestations of exclusion and blamed for HIV infection (22,27) ; this is similar to what happens with drug users, being labelled and socially excluded (6,18,22,27) . We found that interruption of ART was not predominant in this study.…”
Section: Discussionmentioning
confidence: 80%
“…A stigma is considered a defect or a label that defines others, diminishing them through negative stereotypes, discriminatory and prejudiced labels (1,(3)(4) . Thus, in addition to the clinical changes that HIV can bring to people's lives, the stigma can also cause serious social and psychological damage due to feelings of inferiority (1,(4)(5) , which significantly increase anxiety, loneliness, depression and the desire to die, reducing self-esteem and self-confidence, which lead to social and sexual isolation of people living with HIV (4,6) . It is estimated that 36.9 million people live with HIV worldwide (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A falsa associação de que a doença estava restrita a um grupo específico de pessoas favoreceu a disseminação viral para indivíduos que pensavam estar protegidos, sendo esta causa apontada como favorável para a expansão do vírus da imunodeficiência humana (HIV) (SOUZA et al, 2012), em especial para grupos sociais mais vulneráveis (GALVÃO et al, 2013;LEE et al, 2015).…”
Section: A Epidemia Da Aids No Mundo E No Brasilunclassified
“…Assim, a infecção do HIV pode alcançar a todos os grupos, sendo considerado um problema de saúde pública no Brasil e no mundo, e de grandes proporções (GRANGEIRO; CASTANHEIRA; NEMES, 2015), uma vez que, além de poder de disseminação que ultrapassa os limites da dimensão biomédica, é uma patologia clínica incurável, a qual fere os indivíduos em suas áreas psicológicas e sociais, marcando-os por rótulos, como seres condenados por transgredir as regras da sociedade, podendo ainda levá-los à morte (ISHIKAWA et al, 2011;LEE et al, 2015). (BRASIL, 2015).…”
Section: A Epidemia Da Aids No Mundo E No Brasilunclassified